2005
DOI: 10.1099/mic.0.27425-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the age and sex of human hosts on the distribution of Escherichia coli ECOR groups and virulence traits

Abstract: Escherichia coli were isolated from the faeces of 266 individuals living in the Canberra region of Australia. The isolates were characterized for their ECOR group membership (A, B1, B2 or D) and for the presence of 29 virulence-associated traits. Overall, 19?5 % of the strains were members of group A, 12?4 % B1, 45?1 % B2 and 22?9 % D. The frequency with which strains belonging to the four ECOR groups were observed varied with the age and sex of the hosts from which they were isolated. In males, the probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 28 publications
3
99
1
Order By: Relevance
“…Similar results were obtained by others [25,26] who found that sex and age factors had no effect on distribution of phylogroups. Whereas Gordon et al [27] found that in males the probability of isolating A or D strains increased with host age, whilst the probability of detecting a group B2 strain declined, while in females the probability of recovering A or B2 strains increased with increasing host age and there was a concomitant decline in the likelihood of isolating B1 or D strains. The reason for these differences may lie in that Gordon et al [27] had used fecal isolates from patients suffering from gastroenteritis, whereas, our isolates were from healthy volunteers who were not aware of any symptoms at the time of sampling.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar results were obtained by others [25,26] who found that sex and age factors had no effect on distribution of phylogroups. Whereas Gordon et al [27] found that in males the probability of isolating A or D strains increased with host age, whilst the probability of detecting a group B2 strain declined, while in females the probability of recovering A or B2 strains increased with increasing host age and there was a concomitant decline in the likelihood of isolating B1 or D strains. The reason for these differences may lie in that Gordon et al [27] had used fecal isolates from patients suffering from gastroenteritis, whereas, our isolates were from healthy volunteers who were not aware of any symptoms at the time of sampling.…”
Section: Discussionmentioning
confidence: 95%
“…Whereas Gordon et al [27] found that in males the probability of isolating A or D strains increased with host age, whilst the probability of detecting a group B2 strain declined, while in females the probability of recovering A or B2 strains increased with increasing host age and there was a concomitant decline in the likelihood of isolating B1 or D strains. The reason for these differences may lie in that Gordon et al [27] had used fecal isolates from patients suffering from gastroenteritis, whereas, our isolates were from healthy volunteers who were not aware of any symptoms at the time of sampling. Also these researchers' study included a wider age range (0-80 years), while our study included only young ages (18- Table 3: Phylogenetic distribution of virulence genes among fecal E. coli isolates from healthy males and females.…”
Section: Discussionmentioning
confidence: 95%
“…The relative abundances of the main phylogroups of E. coli have been shown to vary with body mass and diet in mammals (Gordon & Cowling, 2003, Escobar-Páramo et al, 2006, with host age and sex in humans (Gordon et al, 2005), and with geographical locality in humans (Tenaillon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Strains of the various phylogroups differ in their phenotypic and genotypic characteristics, in their ecological niches, as well as in their propensity to cause disease (Tenaillon et al, 2010). Strains of the various phylogroups are non-randomly distributed with respect to host species in non-human mammals (Gordon & Cowling, 2003;Carlos et al, 2010), and within humans are nonrandomly distributed with respect to host locality (Tenaillon et al, 2010) and the age and sex of the host (Gordon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The strains used in this study were from two existing E. coli collections. The first collection consists of 685 isolates from Australian reptiles, birds and mammals (Gordon & Cowling, 2003), and the second consists of 619 clinical and faecal isolates taken from humans living in Australia (Gordon et al, 2005). All isolates had been previously assayed for a mitomycin C-inducible colicin phenotype, as described by Gordon et al (1998), and PCR-screened for 11 colicins (B, M, Ia, Ib, E1, E2, E6, E7, K, A, D) and seven microcins (M, L, V, C7, H47, B17, J25) .…”
Section: Methodsmentioning
confidence: 99%